2011
DOI: 10.1111/j.1475-6773.2011.01290.x
|View full text |Cite
|
Sign up to set email alerts
|

International Comparability of Patient Safety Indicators in 15 OECD Member Countries: A Methodological Approach of Adjustment by Secondary Diagnoses

Abstract: International comparisons of health system performance based on unadjusted patient safety indicators are problematic due to suspected coding or ascertainment bias. The model could be an interim approach to provide comparable information on hospital quality, with a long-term goal of improving international consistency in diagnostic reporting in administrative data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 14 publications
3
43
0
4
Order By: Relevance
“…The rates have been adjusted by the average number of secondary diagnoses (Drösler et al, 2011) in order to improve inter-country comparability. Despite this adjustment, results for countries that report less than 1.5 diagnoses per record may be underestimated.…”
Section: Definition and Comparabilitymentioning
confidence: 99%
“…The rates have been adjusted by the average number of secondary diagnoses (Drösler et al, 2011) in order to improve inter-country comparability. Despite this adjustment, results for countries that report less than 1.5 diagnoses per record may be underestimated.…”
Section: Definition and Comparabilitymentioning
confidence: 99%
“…This is due to the use of modified exclusion criteria within the algorithm for the calculation of this indicator. In addition, the patient safety rates have been adjusted by the average number of secondary diagnoses (SDx) (Drösler et al, 2011) in order to improve inter-country comparability. Despite this adjustment, the results for the two countries (Finland and Italy) that are reporting less than 1.5 diagnoses per record may be under-estimated.…”
Section: Definition and Comparabilitymentioning
confidence: 99%
“…Drosler et al 5 6 analysed hospital discharge abstract administrative data from multiple countries and found that the PSI rates varied across countries. The variation in the PSI estimate could be caused by true quality of care differences or by differences in data quality.…”
Section: Introductionmentioning
confidence: 99%